Pengaruh Model Pembelajaran Missouri Mathematics Project Terhadap Kemampuan Koneksi Matematis dan Kemandirian Belajar Siswa SMP - Resti Yuliani; Ena Suhena Praja; Muchamad Subali Noto (Jurnal Elemen, 2018)
This research was aimed to know 1) student activity when using missouri mathematics project model, 2) the influence of missouri mathematics project model on students mathematical connection, 3) differences in mathematical connection ability of experimental class and control class, 4) self regulated learning on missouri mathematics project model. The research was conducted at SMPN 2 Cilimus, the sample was 68 people using quasi experimental design. The result of data analysis obtained in this research are: 1) there is significant effect of learning model misssouri mathematics project equal to 71,1% to student's mathematical connection ability, 2) there is difference of mathematical connection ability between experiment class and control class, 3) self regulated learning getting the teaching using learning missouri mathematics project are in good criteria.